Understanding the 'degree awarding gap' in geography, planning, geology and environmental sciences in UK higher education through peer research. Issue 2 (15th March 2023) - Singh, Shivani; Pykett, Jessica; Kraftl, Peter; Guisse, Abdourahamane; Hodgson, Edward; Humelnicu, Uma Elena; Keen, Natasha; Kéïta, Sarah; McNaney, Niamh; Menzel, Alice; N'dri, Kouadio; N'goran, Kouamé Junior; et al.
ABSTRACT: This paper draws on critical race theory to analyse testimonies from students that help explain why minoritised ethnic communities studying geography, planning, geology and environmental sciences in the UK, have a lesser chance of being awarded a 'good' degree (i.e. an upper second- or first-class), in comparison to White British people. There are very low levels of ethnic diversity across these subject areas. We conducted peer research, including student-led semi-structured interviews at one British university over a five-month period (involving 38 participants in total). Our analysis explores the processes of minoritisation owing to cultures of Whiteness. These relate to teaching and learning spaces, off-campus encounters, university societies, student representation/committees, social interactions, part-time employment and caring responsibilities. We conclude with a call for action to reframe and disassemble the 'degree awarding gap' through student and staff co-design of policies and actions that will not only confront, but also subvert exclusionary cultures of Whiteness in its various manifestations across university life.